2018
DOI: 10.1186/s12886-018-0729-y
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic characterization of human aqueous humor in the cataract progression after pars plana vitrectomy

Abstract: BackgroundWhile pars plana vitrectomy (PPV) has become the third most commonly performed surgery in the world, it can also induce multiple post complications easily. Among them, cataract progression is the most frequent one that can lead to blindness eventually.MethodsTo understand the underlying mechanisms of post PPV cataract progression, we performed comprehensive metabolic characterization of aqueous humor (AH) samples from 20 cataract patients (10 post PPV complication and 10 none PPV cataract) by a non-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…In order to correct post-vitrectomy cataracts, phacoemulsification combined with intraocular lens implantation is usually performed. However, this surgery has challenging features, which include poor pupillary dilatation caused by the postoperative inflammation, more mobility of the posterior capsule due to the absence of the vitreous, loose zonules and pre-existing posterior capsular dehiscence associated with lengthy vitreoretinal surgery, multiple procedures, and vitrectomy involving vitreous base dissection 5,12. Thus, the surgery for post-vitrectomy cataract may have more difficulties and higher probability of complications 13.…”
Section: Discussionmentioning
confidence: 99%
“…In order to correct post-vitrectomy cataracts, phacoemulsification combined with intraocular lens implantation is usually performed. However, this surgery has challenging features, which include poor pupillary dilatation caused by the postoperative inflammation, more mobility of the posterior capsule due to the absence of the vitreous, loose zonules and pre-existing posterior capsular dehiscence associated with lengthy vitreoretinal surgery, multiple procedures, and vitrectomy involving vitreous base dissection 5,12. Thus, the surgery for post-vitrectomy cataract may have more difficulties and higher probability of complications 13.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the TM parameters were generally smaller in the nanophthalmic eyes than in the normal eyes. The diminution of the TM in nanophthalmic eyes may be explained by its dysgenesis, the metabolic dysfunction of the intraocular fluid after surgery, and elevated IOP [ 30 32 ]. The relatively thinner TM in nanophthalmic eyes may indicate inactive aqueous outflow, which could explain the elevated IOP after cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…AH is not only a nutrient supplier and waste transporter but also a mediator for cell-cell communication (Ji et al 2018). Proteomic and transcriptomic analyses have demonstrated that numbers of proteins and miRNAs present in AH (Kim et al 2012;Dunmire et al 2013;Tanaka et al 2014;Soria et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that there are some potential modulators in AH, such as hormones and growth factors, which may be involved in cellular communication between ocular tissues (Coca-Prados and Escribano 2007;Zhang et al 2009;Lee et al 2011). These modulators are associated with the pathogenesis of various eye diseases (Duan et al 2008;Liu et al 2016;Ji et al 2018). For example, high levels of matrix metalloproteinase, inhibitors of metalloproteinases, and transforming growth factor-β2 in AH are significantly associated with the axial length of the eyes in patients with myopia (Jia et al 2014;Zhang et al 2016).…”
Section: Introductionmentioning
confidence: 99%